2020
DOI: 10.3390/app10093004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Vertical Movements of the Earth’s Crust in Poland with the Co-Kriging Method Based on Various Sources of Data

Abstract: The main aim of this study was to evaluate the applicability of the co-kriging method for modeling the vertical movements of the Earth’s crust based on data acquired with the use of precision leveling techniques and measurements conducted by permanent Global Navigation Satellite System (GNSS) stations. Data were processed with the use of empirical, theoretical, and directional variograms (semivariograms), as well as variogram maps. Large-scale spatial variability was determined using polynomial regression. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Less compression is also present in the area of the Galicia-Volyn depression and the regional deflections of the Ukrainian Carpathians. This trend is confirmed in studies of neighboring regions of Poland [Araszkiewicz, et al, 2016;Kowalczyk, 2020]. The compression zone in Zakarpattia region corresponds to the area between SVLV and VYNO stations (see Figs.…”
Section: Legendsupporting
confidence: 70%
See 1 more Smart Citation
“…Less compression is also present in the area of the Galicia-Volyn depression and the regional deflections of the Ukrainian Carpathians. This trend is confirmed in studies of neighboring regions of Poland [Araszkiewicz, et al, 2016;Kowalczyk, 2020]. The compression zone in Zakarpattia region corresponds to the area between SVLV and VYNO stations (see Figs.…”
Section: Legendsupporting
confidence: 70%
“…At the junction of the Galicia-Volyn depression and the edge deflections of the Ukrainian Carpathians, horizontal compression (Δ = -3•10 -8 ) and subsidence of the territory up to -2 mm/year are noticeable. This correlates with the similar dynamics of Poland's neighboring regions [Kowalczyk, 2005[Kowalczyk, , 2020Araszkiewicz, 2016].…”
Section: Legendsupporting
confidence: 67%
“…Another historical study based on measurements from 1953-1958 and 1974-1975 [37] showed values from −2 mm/year to +0.5 mm/year, while the last vertical velocity map developed on the basis of levelling measurements from 1974-1975 and 1998-1999 shows values of approx. −3 mm/year [38]. In turn, the vertical movement velocity map of the Earth's crust in the area of Poland based on the GNSS data in the 2008-2012 period shows values of approx.…”
Section: Characteristics Of the Research Areamentioning
confidence: 97%
“…It must be assumed that the deterministic part is distributed with space, also known as drift or tendency. The best linear estimation process corresponding to this method is called universal Kriging method [77][78][79][80].…”
Section: Plos Onementioning
confidence: 99%